Annulata nova vel minus cognita in Expeditione 'Porcupine' capta - Ehlers, E (Annals and Magazine of Natural History, 1874)
To the Editors of the Annals and Magazine of Natural History. Gentlemen, You would greatly oblige me by giving, as soon as possible, a place in your most valuable Journal to the enclosed paper, containing the diagnoses of new or little-known annelids collected in the 'Porcupine' expedition, and lately examined by me. I am, Gentlemen, Yours truly, E. Ehlers, M.D., P.P.O. Erlangen, March 11, 1874
Kristian Fauchald's Polychaeta DB